STUDENTS’ PERCEPTION TOWARD INTEGRATING WATCHING VIDEOS AND FUN GAMES FOR VOCABULARY MASTERY - Bagus Tara Yoga Saputra (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Vocabulary as English component has an important role in other English skills and improvement component. By several factual case records, vocabulary is considered as most important English component to deliver to the students; also, mostly students get difficult in memorizing and remembering English vocabularies. This fact motivated the researcher to figure out students’ perceptions of new innovation by integrating watching videos and games. To cover up these questions the researcher conducted survey research with 29 participants of class VIII of MTs Al-Muslihuun. To collect the data, the researcher adopted likert scale and open-ended questionnaire to know students perceptions of watching videos and games implementation in vocabulary teaching and learning then analyzed by using descriptive analyses. The research finding shows that there are some synchronized benefits gained based on students’ perceptions by integrating watching videos and games, those are; vocabulary varieties upgrading with 93% positive responses, vocabulary enhancement with 83% positive responses, fun and entertaining with 94% positive responses, and other various benefits with 90% positive responses. Additionally, the researcher also investigated about students’ experiences in learning vocabularies using innovative techniques; 79% participants said yes and fun.